The Effect of Price to Book Value (PBV) and Price Earning Ratio (PER) on Share Prices at PT Gudang Garam Tbk Period 2012-2021 - Sampurnaningsih, Sri R; Arifah, Istinor (ADPEBI, 2022)
The research aims to examine the effect of Price to Book Value (PBV) and Price Earning ratio (PER) on stock prices of PT Gudang Garam Tbk in 2012-2021. The method used is descriptive quantitative method, using SPSS version 25, in carrying out the classical assumption test, hypothesis testing, multiple linear regression analysis and coefficient of determination analysis. The Research sample is the financial statements of PT Gudang Garam Tbk, period 2012-2021 which consists of balance sheet and profit/loss report period 2012-2021. The results of the partial test (t-test) that Price to Book Value (PBV) has a significant positive effect on stock prices; and Price Earning Ratio (PER) has a significant negative effect on stock prices. The results of the simultaneous test (f-test) is that Price to Book Value (PBV) and Price Earning Ratio (PER) have a significant effect on stock prices. Analysis of the coefficient of determination (adjusted R2) is that PBV and PER have contributed 82,3% to stock prices and the remaining of 17,7% was explained by other variables which were not examined in this research.